Evaluation of neonates with open myelomeningocele - (:unkn) unknown (My University, 1999)
Objective: Myelomeningocele is one of the most common dysraphic disorders. The aim of our study is to present the data collected from 42 babies with myelomeningocele, followed in our neonatal intensive care unit postoperatively. Methods: Data collected from 42 babies is evaluated. Results: Most of the cases (95%) were either not diagnosed antenatally or had a late diagnosis. The anatomical locations of the lesions were: 71% lumbar, 17% lumbosacral, 7% thoracolumbar and 5% thoracic. Seven of the babies had complete guadriplegia and 30 cases had paraparesis in their legs. Neurogenic bladder was observed in 24 cases and they were catheterised. Urinary tract infection occurred in 9 of them. Orthopedic deformities were detected in 25 neonates. In their postoperative follow-up, sepsis was diagnosed in 86% of babies operated after 24 hours of life, while only 17% of the cases operated in the first few hours developed sepsis. Conclusion: Because of its high morbidity and mortality, open spinal dysraphism deserves special attention. Babies with late antenatal diagnosis should be delivered in a center where they can be operated soon after birth or, should be referred as soon as possible, preferably in the first 24 hours, if they were born in another hospital.
Keywords: Myelomeningocele; Newborn